Strategi Pemasaran Inovatif dalam Mempertahankan Eksistensi Usaha Kuliner: (Studi Kasus Warung Pecel Kediri Bu Mawar di Kota Pasuruan) - Dias Sasana Eka Safitri; Rini Ratna Nafitasari (Asosiasi Riset Ilmu Manajemen dan Bisnis Indonesia, 2025)
This study examines the innovative marketing strategies implemented by Warung Pecel Kediri Bu Mawar in Pasuruan City in an effort to maintain its existence amidst increasingly competitive culinary business. The main issue raised is how traditional culinary businesses can survive and thrive through adapting effective and sustainable marketing strategies. This study uses Kotler's 4P marketing mix theoretical framework (product, price, place, promotion) and the Theory of 9 Dimensions of Business Success as the basis for analysis. The research method used is a qualitative approach with data collection techniques through in-depth interviews, direct observation, and documentation. The results show that improving product and service quality, menu innovations that are responsive to health trends and consumer preferences, the use of digital media for promotion, competitive pricing, and strategic location selection are key factors in maintaining business sustainability. The integration of digital technology, such as the use of social media and online food ordering applications, has proven effective in expanding market reach, especially among young consumers. The study's conclusion confirms that the combination of product innovation, adaptive promotion, competitive pricing, and the right location is crucial for maintaining the competitiveness and existence of traditional culinary businesses. The practical implications of this research provide strategic guidance for culinary business actors in facing market dynamics and increasing business sustainability through continuous marketing innovation and adaptation.